PEMBINAAN SEKOLAH MENENGAH KEJURUAN KARYA BAHANA MANDIRI DALAM BENTUK PELATIHAN UJI RESISTENSI ANTIBIOTIK (STIKes Mitra Keluarga, 2024)
Introduction: Antimicrobial resistance (AMR) remains a public health problem. Increased antimicrobial resistance in microbial pathogen can cause death due to inappropriate treatment. The aim of this community service was educational training regarding antibiotic resistance test practice for students at Karya Bahana Mandiri Vocational School so that they have experience and insight into antibiotic resistance testing procedures. The activity was conducted in November 2023. The community service was held as seminar and workshop practice. We Collected data regarding the knowledge of students at Karya Bahana Mandiri Vocational School, answered pre and post-test questionnaires, then the data has been analyzed descriptively. The results of the activity were 75 respondents consisting of 73 students and 2 teachers. The pretest and post-test results showed an increase in participants' knowledge regarding antibiotic resistance, which has average score from 61 (73 participants) to 77 (66 participants), respectively. The analysis showed that this activity can increase participants' knowledge of antibiotic resistance testing procedures as one of the competencies needed as a competent medical laboratory technologist in the future.